2014
DOI: 10.3892/etm.2014.1696
|View full text |Cite
|
Sign up to set email alerts
|

Indole-3-carbinol inhibits nasopharyngeal carcinoma cell growth in vivo and in vitro through inhibition of the PI3K/Akt pathway

Abstract: Indole-3-carbinol (I3C) is an active component of cruciferous vegetables and has been shown to markedly inhibit the growth of a variety of tumors. However, the role of I3C in nasopharyngeal carcinoma (NPC) remains unclear. Thus, the aim of the present study was to investigate the inhibition of NPC cells by I3C in vitro and in vivo. The human CNE2 NPC cell line was treated with various concentrations (0, 100, 200 and 300 μM) of I3C and analysis of cell proliferation after 0, 24, 48 and 72 h, apoptosis after 48 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…These results suggest that AMPK and SIRT1 activate each other and jointly regulate their downstream effector PGC-1 α in mesangial cells [ 42 , 43 ]. High glucose levels can prevent mesangial cells from transitioning from G1 to S phase, reduce the proportion of cells in G1 phase, increase the proportion of cells in S phase, and promote DNA synthesis and cell proliferation [ 44 ]. Consistent with our results, several recent studies have demonstrated that adiponectin [ 45 ] or AICAR [ 46 ] protect renal podocytes and decrease albuminuria in diabetic animals by decreasing oxidative stress and apoptosis via a mechanism involving the activation of AMPK.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that AMPK and SIRT1 activate each other and jointly regulate their downstream effector PGC-1 α in mesangial cells [ 42 , 43 ]. High glucose levels can prevent mesangial cells from transitioning from G1 to S phase, reduce the proportion of cells in G1 phase, increase the proportion of cells in S phase, and promote DNA synthesis and cell proliferation [ 44 ]. Consistent with our results, several recent studies have demonstrated that adiponectin [ 45 ] or AICAR [ 46 ] protect renal podocytes and decrease albuminuria in diabetic animals by decreasing oxidative stress and apoptosis via a mechanism involving the activation of AMPK.…”
Section: Discussionmentioning
confidence: 99%
“…According to their results, as the concentration of I3C increased, in PI3K/Akt pathway associated proteins levels and cell proliferation was decreased while there was an increase in apoptosis. Also in the prevention and treatment groups of mice, there was the development of small tumors and also the levels of PI3K/Akt pathway proteins were reduced (Mao et al, 2014 ).…”
Section: Indole-3-carbinolmentioning
confidence: 99%
“…Nasopharyngeal carcinoma (NPC) is a malignant tumor that occurs on the top and lateral wall of nasopharyngeal cavity [1] . The tumor originates from the epithelial cells covering the nasopharyngeal surface [2] . NPC is a geographically relevant tumor with a particular global distribution and complex etiology, with higher incidence in Southern China, Southeast Asian countries, Northern and Northeastern Africa, Alaska of the United States, and Western Canada [3] .…”
Section: Introductionmentioning
confidence: 99%